PENGARUH PEMANFAATAN ABU KERAK BOILER CANGKANG KELAPA SAWIT SEBAGAI BAHAN TAMBAHAN (ADMIXTURE) SEMEN TERHADAP KUATTEKAN MORTAR - 66-74 . Jamizar (Universitas Negeri Padang, 2013)
This research experiment, the study population is a mortar made ​​from a mixture of cement, sand, gray scale boiler, water with cement of the same weight. For the sample in this study was sampled mortar and sample materials. Sample testing of concrete cube of size 5 cm x 5 cm x 5 cm by 54 pieces of the specimen. The data used in this study is primary data is data taken directly to the object of researchers by making and testing of the specimen. From the research shows that, by using gray scale oil palm shell boiler influential as mortar additives, compressive strength reached an optimum value is 18.873 MPa at 15% with a variation of the addition of water absorption power 17, 441% does not exceed the value of the control mortar compressive strength 19.026 MPa 14.965% water absorption power. Crust boiler ash can be used as a substitute for sand crust boiler ash containing carbon that are hard like sand element. Key words : mortar, abu crust boiler shells palm oil, cement, sand and water